2008
DOI: 10.1007/s00436-008-0930-7
|View full text |Cite
|
Sign up to set email alerts
|

The type and mysorensis forms of the Anopheles stephensi (Diptera: Culicidae) in India exhibit identical ribosomal DNA ITS2 and domain-3 sequences

Abstract: Anopheles (Cellia) stephensi Liston 1901 is one of the major malaria vectors in the Indian subcontinent, Iran, and the Middle East. Three races in this species, namely A. stephensi stephensi (type form), A. stephensi variety mysorensis, and A. stephensi intermediate form, have earlier been reported by several investigators. We describe here the sequencing of the ribosomal DNA internal transcribed spacer 2 (ITS2) and domain-3 (D3) loci of the A. stephensi type and variety mysorensis forms. We also sequenced fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…But then again, the inconsistent range of ridge numbers, identical nucleotide sequences of ITS2 and D3 loci in type and mysorensis, and the identity of COII sequences between Indian type form and Iranian mysorensis suggest these markers are not suitable for the identi cation of biological forms of An. stepehnsi [24,28,29,30,31]. Our analysis also supports these results since we were unable to recognize (the biological form) our lab strain using COI, COII and ITS2.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…But then again, the inconsistent range of ridge numbers, identical nucleotide sequences of ITS2 and D3 loci in type and mysorensis, and the identity of COII sequences between Indian type form and Iranian mysorensis suggest these markers are not suitable for the identi cation of biological forms of An. stepehnsi [24,28,29,30,31]. Our analysis also supports these results since we were unable to recognize (the biological form) our lab strain using COI, COII and ITS2.…”
Section: Discussionsupporting
confidence: 82%
“…The COI and COII, ITS2 and D3 based analysis from Iran and India have revealed extensive gene ow among these variants [30,31] whereas other genetic studies (using microsatellite markers) have demonstrated a signi cant genetic differentiation and non-signi cant gene ow among them with type and intermediate being more closely related genetically [32]. These biotypes with taxonomic identities and differential vector competencies may contribute to the current epidemiological situations [24].…”
Section: Discussionmentioning
confidence: 95%
“…stephensi still under genetic dissociation within its different biological forms including, type, Intermediate and mysorensis, and is considered as a suspected cryptic species complex. ITS2 and D3 loci showed identical nucleotide sequences in type and mysorensis biological forms suggested that these molecular markers are not suitable for the identification of biological forms [ 35 ]. On the other hand, Anopheles persiensis was characterized and named principally as a new record to the world and Iranian Anopheles fauna based on DNA evidence for the first time [ 36 ] without any crossing experiment between An.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Alam et al (2008) have demonstrated that the ‘ type ’ and variety ‘ mysorensis ’ forms of An. stephensi exhibited identical nucleotide sequences at ITS‐2 and D3 loci.…”
Section: Introductionmentioning
confidence: 99%